m Musykilatu Istikhdami Sparkol Videoscribe li ta’limi al-Lughah al-‘Arabiyah Bi Maharati al-Qira’ah Lada Thalabati STIT Miftahul Ulum Bangkalan. - azhari, Jalaludin Faruk; asyhari (Lisan An Nathiq : Jurnal Bahasa dan Pendidikan Bahasa Arab, 2023)
The difficulties in learning Arabic are a barrier to the implementation of Arabic language learning and instruction. The purpose of this study is to identify the issue with utilizing Sparkol Videoscribe to teach Arabic to Maharah Qira'ah students at STIT Miftahul Ulum Bangkalan. Because the data given will be in descriptive form, employing phenomenological research, the qualitative approach is the fundamental foundation for this research technique. The findings of this study are summarized in the first few points: there was no impression or motivation prior to learning in the preparation phase, and suitable tools and equipment were available. The second point, the implementation phase, gives research indicating that the videoscribe visualization and presentation provide greater animation than material content, in addition to the requirement for